PENGARUH METODE PEMBELAJARAN DAN TIPE KEPRIBADIAN TERHADAP HASIL BELAJAR MATEMATIKA - Ismet (AS-SALAM, 2015)
This study aimed to find out the effect of Role Playing Method macro and micro And Personality Type to a increase mathematic learning chievement.This research represent the quantitative research of comparability use the experiment method by desain.The result of study shows: (1) the students achievement mathematic who studied by macro role playing method was higher than those who studied by micro role playing method, (2) the student who had exstrovert type studied by macro role playing method had higher on mathematic learning achievement than those who had extrovert type and studied by micro role playing method, (3) the student who had introvert type and studied by micro role playing method had higher on mathematic learning achievement than those who introvert type and studied macro role playing method and (4) there was an interaction effect between the use of role playing method and personal type Some implications of this study were: appliying role playing micro and macro method in mathematics learning, should be considered the personal type (ekstrovert and introvert).